Prevalence and genotype distribution of human papillomavirus in individuals referred to a laboratory in Rey City, Iran - Omid Salahi Ardekani; Nasim Bashiri; Arash Letafati; Saber Taheri; Fateme Sadat Hashemi Pasand; Mojgan Rahmanian; Alireza Shikki; Shima Sadeghipour Marvi; Mohammad Javad Lakzian; Sheida Sarrafzadeh; Nasim Rafinezhad; Behnam Molavi; et al. (Discover Social Science and Health)
Abstract Background and aim Human papillomavirus (HPV) is a common sexually transmitted infection linked to various cancers and most sexually active individuals are at risk of contracting it. Understanding regional genotype distribution is essential for establishing effective prevention programs. Therefore, this research focused on analyzing the distribution of HPV genotypes among individuals referred to a laboratory in Rey City, Iran. Material and method This study, conducted from September to December 2024 in Rey City, Iran, analyzed genital specimens from female patients. The Favorgen Biotech Corp kit (FAVORGEN, Taiwan) was used for DNA extraction, and the CLART® HPV4 kit (GENOMICA, Spain) was used for PCR and genotyping. Data were analyzed at individual and genotype levels using frequency analysis and statistical analysis was performed with IBM SPSS-27. Results Out of the 722 females tested, 195 (27%) were found to be HPV-positive. Among those infected, 29.2% carried only high-risk (HR) genotypes, while over 36.9% had only low-risk (LR) genotypes. Additionally, 23.6% of individuals tested positive for both HR and LR genotypes. The prevalence of HR genotypes was highest among individuals aged 25 to 34 (54%). The genotypes that appeared most frequently included HPV-6 (13.8%), HPV-16 (7.4%), HPV-39 (6.6%), and HPV-54 (6.3%), while HPV-26 and HPV-43 were each detected in only one case. Conclusion This study found a significant HPV prevalence in females in Rey City, especially those under 25 and aged 25–34, highlighting the need for age-targeted prevention. Since current vaccines do not cover HPV-39 and HPV-54, the findings provide valuable data for future vaccination policies in Rey City, Iran.